Comparative formability study of natural rubber, B-nitrile rubber and silicon rubber in rubber assisted forming of hemispherical copper cup - Kumar, Abhishek; Kumar, Santosh; Ram, Dasharath (Transstellar Journal Publications and Research Consultancy Private Limited (TJPRC), 2018)
Rubber assisted sheet metal forming has always been the subject of research for last 50 years. Rubber diaphragm is primarily used to improve the formability of the sheet metal components having complex features. In this paper, three varieties of rubber viz. Natural rubber, B-nitrile rubber and Silicon rubber are used to form the hemispherical part made out of pure copper. The rubbers are manufactured in such a way to achieve the same hardness level so that proper comparison could be made. The same part is formed under three rubber diaphragms and thickness reduction is compared. The present paper gives the detail account of rubber chemical composition, forming set up and comparison of thickness reduction in the part after forming.
Keywords: Formability; Grid analysis; Natural rubber